(untitled) (Journal of Libya for geographical studies, 2025)
The evolution of housing patterns and their diversity reflect the development of populations, as well as the civilizational, cultural, social, and economic indicators that reflect the extent to which natural environmental elements are taken into account when designing and building homes. This paper aims to study the most important factors that have influenced the evolution of housing patterns in the city of Zintan, especially the topographic factor, which has been shown to have a clear impact on housing patterns in the region. The topography of the area, the natural environmental resources, and the economic status of the population have all contributed to the evolution of housing patterns in the city of Zintan. Field study has revealed that housing patterns in the study area have evolved over the years from underground dwellings (caves or domes) during the time of the ancestors (the Turkish era and before) to more modern dwellings, including what is commonly referred to as the "Arabian house" in the second half of the last century, and finally to modern homes with a Western European style at present. It has also been shown that the primary factor driving this evolution is the topographic factor, along with a range of other factors including the quality and availability of building materials, improved living standards, and the availability of necessary funds for construction. Based on the results obtained, the study recommended a number of recommendations, one of the most important being the necessity of preserving many of the old housing patterns as they represent a cultural and historical heritage highlighting the personality of the region and its history, which can be the basis for many tourism activities and cultural festivals.